STRUKTUR INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Amir Machmud (Universitas Negeri Medan, 2014)
This study aims to analyze the structure of Islamic banking industry in Indonesia after the issuance of Law No. 21 of 2008 on Islamic Banking, including the factors that influence the structure industro through concentration ratio. The method used in this study was a descriptive study (descriptive study) and correlational studies, collecting data through observation techniques to data released by the Financial Services Authority and Bank Indonesia. The data that has been collected analyzed using the ratio of the concentration of 4 largest companies and non-parametric statistical test through Pearson product moment correlation to determine the relationship between variables that affect the concentration ratio. Based on the results of the study showed that the structure of the Islamic banking industry in Indonesia after Act No 21 of 2008 is included in the criteria but with a tight oligopoly involving Islamic Business Unit (UUS) and sharia rural banks (BPRS) included in the competition category is p. The structure of the industry has had a negative relationship with the share market, absolute capital and government policies, and have a positive relationship with the economies of scale and market growth.